(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
This paper offers a partial report of an interdisciplinary study of the ways Italo Calvino’s phraseology has been translated Tradurre verbi polirematici in tedesco. Analisi de Il sentiero dei nidi di ragno (1947) di Italo Calvino Sabine E. Koesters Gensini SAPIENZA UNIVERSITÀ DI ROMA (ITALIA) into 16 different languages. For the conference, I focus on the novel Il sentiero dei nidi di ragno (1947) and its translation in German. Firstly, I will describe the principal morphosyntactic, lexical as well as textual features and examine the ways they are expressed in the German current translation. Secondly, a classification of the different equivalents, a constitution of a corpus made of only light verb equivalents, and a critical discussion of the German corpus along the same guidelines for the original, Italian versions is offered. Finally, it will be suggested that the two corpora elicited will provide a good basis for interlinguistic comparison, at both the theoretical and the applied level, with particular attention for Translation of phraseology and/or Didactics of phraseology.